40. MULTIMORBIDITY AND POLYPHARMACY IN OLDER ADULTS AT THE FAMILY PHYSICIAN CLINICS, LE VAN THINH HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To determine the prevalence of multimorbidity, polypharmacy, and their associations with demographic factors among older adults attending the family doctor clinic at Le Van Thinh Hospital.Objects and methods: A cross-sectional retrospective study was conducted on medical records of 351 patients aged 60 years and older who attended the family doctor clinic at Le Van Thinh Hospital from October to December 2022. Multimorbidity was defined as having three or more chronic conditions, and polypharmacy as taking five or more different medications.Results: The prevalence of multimorbidity among older adults was 94.9%, and that of polypharmacy was 54.1%. Older adults aged 75 years or older had a significantly higher risk of polypharmacy compared to those aged 60-74 years (OR = 2.03; 95% CI: 1.21-3.39; p = 0.007). No significant associations were found between other demographic factors and multimorbidity or polypharmacy.Conclusion: Multimorbidity and polypharmacy are highly prevalent among older adults attending the family doctor clinic, especially in those aged 75 years or older. These findings highlight the importance of comprehensive management and rational prescribing for elderly patients at primary care facilities.
Keywords: Multimorbidity, polypharmacy, older adults, family medicine, primary care.